Methodological approach for creating an IoT manufacturing application - Rahmouni, A. (2021)
With the heterogeneity and diversity of electronic systems and their memory capacity, the Internet of Things technologies face several challenges, such as the difficulty in choosing a growing catalogue of IoT technologies and the lack of interoperability of these technologies. This leads to the creation of particular IoT architectures and to the selection of IoT technologies by trying and error approaches. We propose a methodological approach for creating an IoT application guided by the users’ needs and by the contextual environment. It enables the user to select the right hardware guided by the market supply and to check the performances of the IoT solutions. We implement and test our proposition in a picking system of a manufacturing factory. This practical implementation provides feedback regarding our methodological approach for creating an IoT application, which in turn enables us to improve and remodel the approach.